Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

how do you simplify this ? 8(x - 4) - 6(x - 1) + 9x

Sagot :

[tex]8(x-4)-6(x-1)+9x\\\\=8\cdot x+8\cdot(-4)-6\cdot x-6\cdot(-1)+9x\\\\=8x-32-6x+6+9x\\\\=(8x-6x+9x)+(-32+6)\\\\=\boxed{11x-26}[/tex]
[tex]8(x - 4) - 6(x - 1) + 9x=\\ 8x-32-6x+6+9x=\\ 11x-26[/tex]